Proclus on Whole and Part: A Reappraisal of Mereology in Neoplatonic Metaphysics - Oosthou, Arthur, (Classical Studies E-Books Online, Collection 2025., 2025)
No late ancient philosopher has written more extensively on part-whole relations than the Neoplatonic commentator Proclus. In Proclus on Whole and Part , Arthur Oosthout unfolds, for the first time, Proclus' detailed and systematic analysis of (Neo-)Platonic mereology in full. Oosthout weaves together a great number of previously disconnected scholarly inquiries into Proclus, while adding many critical notes and new insights of his own. He bases this new synthesis on a detailed theoretical framework built not only on the metaphysical theories of Plato and Aristotle, but also on the arguments of prominent scholars of modern mereology.